Utilization of Spent Rice Straw Compost to Substitute Napier Grass Fed to Cattle and Its Effect on Rumen Metabolism Products - Suwandyastuti, SNO; Bata, M (ANIMAL PRODUCTION, 2012)
Abstract. The aim of this research was to find the optimum level of substitution of fresh Napier Grass with Spent Rice Straw Compost (SRSC) on rumen metabolism products. Two male cattle breeds consisted of indigenous cattle (Ongole Crossbred = OC) with average body weight of 78.48±7.69 kg  and Fries Holland Crossbred (FHC) with body weight of 83.93±17.67 kg were kept in individual cages of 1x1.2 m and they were given  four kinds  of Napier Grass subtituted with SRSC of 0, 25, 50 and 75 percent of forage dry matter. Therefore, factorial experiment of 2x4 was used in this research. The dry matter ratio of forage and concentrate was maintained at 50:50% with total dry matter intake 3% of body weight. Total Volatil Fatty Acid (VFA) production were influenced by the breed of cattle and the body weight, but there was no significant effect of breed on the N-NH3.  Both average of VFA (122.92±3.22 mM/l) and N-NH3 (4.14±0.4 mM/l) were still in the optimum range for rumen micoorganisme activities. Regression analysis showed that the digestibility of crude fiber had same pattern with acetate (C2), propionate (C3), butirate (C4), and valerate (C5). It can be concluded that SRSC can be used to substite fresh Napier Grass up to 75 percent of forage dry matter  in the diets of male cattle both OC and FHC. Keywords : Spent compost, Volatile Fatty Acid, Nitrogen Ammonia Abstrak. Tujuan dari penelitian ini adalah untuk menemukan level optimum susbsitusi rumput gajah dengan kompos jamur merang ditinjau dari produk-produk metabolisme rumen. Dua jenis bangsa sapi berkelamin jantan dari bangsa Peranakan Ongole (PO) dengan rataan berat badan 78,48 ± 7,69 kg dan bangsa sapi Peranakan Fries Holstein (PFH) dengan rataan berat badan 83.93 ± 17,67 kg dipelihara pada kadang individu dengan ukuran 1 x 1.2 m. Sapi-sapi tersebut diberi empat macam  pakan subsitusi rumput gajah dengan kompos jamur merang dengan taraf 0, 25, 50 dan 75%  dari bahan kering rumput. Penelitian ini menggunakan pola faktorial. Imbangan bahan kering hijauan dan konsentrat adalah 50:50% dengan  total konsumsi bahan kering  3% dari bobot hidup sapi. Produksi total VFA dipengaruhi oleh bangsa dan bobot badan sapi, tetapi produksi N-NH3 tidak dipengaruhi oleh baik bangsa, bobot hidup maupun  taraf subsitusi. Rataan VFA (122.92 ± 3.22 mM/l) dan N-NH3 (4.14 ± 0.4 mM/l)  masih dalam kisaran optimum untuk aktivitas mikroorganisme rumen. Analisis regresi menunjukkan bahwa koefisien cerna serat kasar mempunyai pola yang sama dengan produksi asetat, propionate, butirat dan valerat. Kesimpulannya kompos jamur merang dapat menggantikan rumput gajah sampai dengan 75%  dari bahan kering rumput untuk diberikan pada sapi jantan baik bangsa PO maupun PFH.Kata kunci : kompos jamur merang, VFA, Nitrogen Ammonia SNO Suwandyastuti and M Bata/Animal Production 14(3):147-154, September 2012